EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN MORPH POWERPOINT TERHADAP PENINGKATAN HASIL BELAJAR SENI BUDAYA SISWA KELAS VII SMP NEGERI 3 PANCA RIJANG - Kasman; Abd. Kahar; Nurmayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of using Morph PowerPoint in improving the learning outcomes of seventh grade students in Arts and Culture at SMP Negeri 3 Panca Rijang. This study used a true experimental method with a pretest-posttest control group design. The population in this study was 67 seventh grade students, while the research sample consisted of an experimental class (VII.1) and a control class (VII.3), each consisting of 23 students. The instrument used was a multiple-choice test given before and after the treatment. The results showed that the average pretest score of the experimental class was 50.43, which increased to 91.52, while the control class experienced an increase from 48.04 to 81.52. The N-Gain analysis showed that the experimental class had a score of 82.94% (effective) and the control class 63.33% (quite effective). Thus, it can be concluded that Morph PowerPoint is proven to be effective in improving students' learning outcomes in Arts and Culture.